IMPLEMENTATION STATUS AND BARRIERS OF GOOD MANUFACTURING PRACTICE (GMP) FOR CHINESE PATENT MEDICINE - He, Tian Tian; Hu, Hao; Wang, Yi Tao (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Safety, quality and effectiveness of Chinese patent medicine (CPM) are highly relevant to the manufacturing process. However,the level of manufacturing practice (GMP) for CPM as implemented in China is less reported in literatures. Therefore, the aim of this paper wasto reveal the implementation status of GMP for CPM in China, in terms of implementation principle, implementation content, industrial impacts,and implementation barriers from both macro and micro aspects.Methods: A comprehensive analysis was carried out with archival data and field work at CPM manufacturers.Results: Both implementation principle and content of GMP for CPM in China indicated a transformation from provision-oriented tohuman-oriented, leaving more flexible operation space to CPM manufacturers. However, poor manufacturing practices may still exist becausethe implementation of GMP in China is not strict enough to eliminate all the unqualified CPM manufacturers from market. Moreover, comparedwith international WHO GMP, there are barriers for implementing GMP for CPM, including main deficiencies in quality control management,cost of GMP renovation projects, lack of education and training, and lack of expertise.Conclusion: This paper found that the implementation of GMP for CPM still faced many barriers though GMP had generated some positiveimpacts on CPM manufacturing. Removal of implementation barriers could be considered, including strengthening personnel competence,improving the quality management system and enhancing the international communication with advanced GMP regulators.